Insights into the role of three Endonuclease III enzymes for oxidative stress resistance in the extremely radiation resistant bacterium Deinococcus radiodurans - Rollo, Filipe; Martins, Guilherme D.; Gouveia, André G.; Ithurbide, Solenne; Servant, Pascale; Romão, Célia V.; Moe, Elin (Frontiers in Microbiology, 2023)
The extremely radiation and desiccation resistant bacterium Deinococcus radiodurans possesses three genes encoding Endonuclease III-like enzymes (DrEndoIII1, DrEndoIII2, DrEndoIII3). In vitro enzymatic activity measurements revealed that DrEndoIII2 is the main endonuclease in this organism, while DrEndoIII1 and 3 possess unusual and, so far, no detectable EndoIII activity, respectively. In order to understand the role of these enzymes at a cellular level, DrEndoIII knockout mutants were constructed and subjected to various oxidative stress related conditions. The results showed that the mutants are as resistant to ionizing and UV-C radiation as well as H2O2 exposure as the wild type. However, upon exposure to oxidative stress induced by methyl viologen, the knockout strains were more resistant than the wild type (WT). The difference in resistance may be attributed to the observed upregulation of the EndoIII homologs gene expression upon addition of methyl viologen. In conclusion, our data suggest that all three EndoIII homologs are crucial for cell survival in stress conditions, since the knockout of one of the genes tend to be compensated for by overexpression of the genes encoding the other two.